Anticonvulsant effects of phenobarbital and primidone during ontogenesis in rats - Kubova, H; Mares, P (Epilepsy research, 1991)
The influence of phenobarbital (PHB, 10, 20, 40 or 80 mg/kg i.p.) and primidone (PRI, 40 or 80 mg/kg i.p.) on metrazol-induced motor seizures was studied in rats 7, 12, 15, 18, 25 and 90 days old. PHB blocked both types of seizures induced by metrazol-minimal (mMS) as well as generalized tonic-clonic (MMS)--in all age groups where they appeared under control conditions. The effect against major seizures was always better expressed than against mMS. Pretreatment with PHB led to the appearance of mMS in 7- and 12-day-old rat pups, where control animals did not exhibit this type of seizure. Combined administration of the 2 high doses of PHB and metrazol resulted in the appearance of behavioral automatisms in young rats. PRI abolished MMS in adult rats only, no changes were seen in 25-day-old animals and specific suppression of the tonic phase of MMS was observed in younger rats. mMS were influenced only in 7- and 12-day-old rats, where an increase in their incidence was recorded. Pretreatment with PRI never induced automatisms. The different actions of PHB and PRI speak in favor of an anticonvulsant action of PRI itself.
Keywords: Pentylenetetrazole; Seizures; primidon; Prohibitins; Rats, Inbred Strains; záchvaty; Automatism; krysa rodu Rattus; zvířata; pentylentetrazol; Morphogenesis; morfogeneze; Phenobarbital; Rats; Animals; automatismus; Primidone; fenobarbital; inbrední kmeny potkanů; prohibitiny